At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Write an equation for the nth term of the arithmetic sequence. -6,-9,-12,-15

Sagot :

Answer:

[tex]a_{n}[/tex] = - 3n - 3

Step-by-step explanation:

The nth term of an arithmetic sequence is

[tex]a_{n}[/tex] = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

Here a₁ = - 6 and d = a₂ - a₁ = - 9 - (- 6) = - 9 + 6 = - 3 , then

[tex]a_{n}[/tex] = - 6 - 3(n - 1) = - 6 - 3n + 3 = - 3n - 3

We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.